2014
DOI: 10.1016/j.rgmxen.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Mexican consensus on the diagnosis and management of hepatocellular carcinoma

Abstract: Introduction: There has been an increase in the incidence of hepatocellular carcinoma (HCC) worldwide and information on this disease is limited in Mexico. Aims: To analyze the available evidence on the diagnosis and treatment of HCC in the Mexican population. Material and methods: The Mexican Association of Hepatology organized a meeting that 24 medical specialists interested in HCC attended. An electronic database search was carried out to identify documents published from 2000 with the keywords «Hepatocellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…In the population studied, the highest mortality rates were observed in the group aged > 60 years, which agrees with earlier data for Mexico. 8,10 In addition, both sexes seemed to suffer equally from HCC in 2014, 8 although most authors have reported higher mortality rates for men in Mexico 5,6 and Latin America. 2 In the present study in 2019, a higher death rate among women aged < 60 years was found in Hidalgo, although men were more affected than women in the three municipalities with the highest HCC death figures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the population studied, the highest mortality rates were observed in the group aged > 60 years, which agrees with earlier data for Mexico. 8,10 In addition, both sexes seemed to suffer equally from HCC in 2014, 8 although most authors have reported higher mortality rates for men in Mexico 5,6 and Latin America. 2 In the present study in 2019, a higher death rate among women aged < 60 years was found in Hidalgo, although men were more affected than women in the three municipalities with the highest HCC death figures.…”
Section: Discussionmentioning
confidence: 99%
“…Better information might improve early detection and thus decrease morbidity and mortality among HCC patients. 7,8,10 I Hidalgo State, Mexico, had an economic complexity index (ECI) of -0.68 in 2021 and ranked 21 st among the country's 32 states, while the overall ECI for Mexico was 1.31 in 2020. Over 43.8% of Hidalgo's population live in poverty, and the average illiteracy rate in 2020 was 6.6%.…”
Section: Introductionmentioning
confidence: 99%